2002
DOI: 10.1152/ajpcell.01273.2000
|View full text |Cite
|
Sign up to set email alerts
|

Redox states of type 1 ryanodine receptor alter Ca2+ release channel response to modulators

Abstract: The type 1 ryanodine receptor (RyR1) from rabbit skeletal muscle displayed two distinct degrees of response to cytoplasmic Ca2+ [high- and low-open probability ( P o) channels]. Here, we examined the effects of adenine nucleotides and caffeine on these channels and their modulations by sulfhydryl reagents. High- P o channels showed biphasic Ca2+ dependence and were activated by adenine nucleotides and caffeine. Unexpectedly, low- P o channels did not respond to either modulator. The addition of a reducing reag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 43 publications
5
49
0
Order By: Relevance
“…Additionally, the redox status of RyR, which is possibly influenced by decreased PO 2 , can alter Ca 2ϩ release (16). One hypothesis from this investigation is that an increase in RyR expression could lead to altered hypoxia-induced Ca 2ϩ sparks and saturation of any oxygen-sensitive hyperpolarization response.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, the redox status of RyR, which is possibly influenced by decreased PO 2 , can alter Ca 2ϩ release (16). One hypothesis from this investigation is that an increase in RyR expression could lead to altered hypoxia-induced Ca 2ϩ sparks and saturation of any oxygen-sensitive hyperpolarization response.…”
Section: Discussionmentioning
confidence: 87%
“…*, p Ͻ 0.01. Recent studies have demonstrated that RyaR activity can be enhanced by its redox state (45)(46)(47). Preincubation with the reducing agent, DTT, completely abolished the ability of C8-GlcCer (Fig.…”
Section: Fig 1 Lipids Used In This Study and Their Abbreviationsmentioning
confidence: 87%
“…Skeletal RyR1 channels have a few cysteine residues highly responsive to oxidative modification at physiological pH (65), a property that makes them likely candi- dates to act as intracellular redox sensors (66,67). In vitro experiments indicate that oxidation/alkylation, S-nitrosylation (38,68), or S-glutathionylation (38,62) of RyR1 hyperreactive SH residues enhances channel activity, whereas reduction to their free sulfhydryl state has the opposite effect (67)(68)(69)(70)(71)(72). In particular, incubation of isolated SR vesicles with superoxide anion or H 2 O 2 promotes RyR activation (42,(73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%